Patent Foramen Ovale and Cryptogenic Stroke: Challenges in Diagnosis and Management - Yafi, Dhanang Ali; Azmi, Azmi (The Indonesian Heart Association, 2021)
A patent foramen ovale (PFO) is a common disorder that affects between 20-34% of the adult population. This condition is a benign finding for most people. However, In some the PFO can open widely and enabling paradoxical embolism to transit from venous to arterial circulation, which is associated with stroke and systemic embolization. There are still unclear to date regarding the effectiveness of pharmacological anticoagulant therapy, defined as antithrombin or antiplatelet therapy, which has proven to be more beneficial for patients with PFO and cryptogenic stroke. In addition, surgical and transcutaneous PFO closure has been proposed for secondary prevention of stroke in patients with cryptogenic stroke with PFO. Both catheter-based and surgical modes of closure have been shown to reduce the incidence of subsequent embolism substantially. This review will discuss the evidence regarding the relationship between PFO and cryptogenic stroke and decision making for management strategies.